2014
DOI: 10.1080/09540121.2014.921276
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial burdens negatively impact HIV antiretroviral adherence in gay, bisexual, and other men who have sex with men aged 50 and older

Abstract: We sought to characterize HIV antiretroviral therapy (ART) adherence and psychosocial correlates of adherence in a sample of gay, bisexual, and other non-gay or –bisexual identified MSM ages 50 and over. As part of a cross-sectional study we recruited a community-based sample of 199 men and assessed adherence to current ART medications along four domains: 1) missing doses in the past 4 days, 2) taking doses on the specified schedule in the past 4 days, 3) following instructions about how to take the medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Six investigations found that stigma was significantly associated with poor self-reported adherence at the multivariate level, after adjusting for factors such as demographics, perceived health, structural barriers, and alcohol and drug use [42,44,45,47,49,56]. Two prospective investigations lent support to this association as well.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 73%
See 2 more Smart Citations
“…Six investigations found that stigma was significantly associated with poor self-reported adherence at the multivariate level, after adjusting for factors such as demographics, perceived health, structural barriers, and alcohol and drug use [42,44,45,47,49,56]. Two prospective investigations lent support to this association as well.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 73%
“…PLWH who have experienced discrimination, stereotyping, or prejudice from others (i.e., enacted stigma), or who anticipate these experiences (i.e., anticipated stigma), may fear disclosing their HIV status. The complexity of medication regimens can interfere with PLWH's ability to conceal HIV status because it can require pill taking at inopportune times and in public settings [47]. Anticipated or enacted stigma may produce concerns about potentially revealing one's HIV status when accessing or consuming medications.…”
Section: Concerns About Inadvertent Disclosure Of Hiv Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Halkitis and colleagues found depression to be associated with poorer antiretroviral therapy adherence in a sample of 180 HIV-positive MSM in New York City. 15 The mental health studies in this issue, along with other recent research, reinforce the impact depression and other mental health issues can have on older HIV-positive adults. Treatment adherence and efficacy of secondary prevention strategies can be impacted by depressive symptoms.…”
Section: Resultsmentioning
confidence: 74%
“…Stress, emotional reactivity, and avoidant coping behaviors contribute to HIV progression through increases in nonadherence (Martinez et al., 2012). Additionally, aging-associated complexities may exacerbate the effects of stress on nonadherence in PLWH aged 50 and older (Halkitis et al., 2014, Warren-Jeanpiere et al., 2014, Wu et al., 2014). Notably, cognitive functioning is a predictor of medication management and nonadherence (Wagner, 2002, Hinkin et al., 2004), and the strength of the predictive capacity increases with age (Frain et al., 2014).…”
Section: Setting the Stage: Interactions Of Hiv Stress And Cognitionmentioning
confidence: 99%